When human cells meet bacteria: precision medicine for cancers using the microbiota - Zhang, Han (Am J Cancer Res, 2018)
The human microbiota interacts with the host immune system in multiple ways to influence the development of diseases, including cancers; however, a detailed understanding of their relationship is unavailable. Accumulating evidence has only revealed an association rather than a causal link between microbial alterations and carcinogenesis. The regulatory loops among the microbiome, human cells and the immune system are far more complicated and require further studies to be revealed. In this review, we discuss the impact of the microbiota on cancer initiation, development and progression in different types of human cells, mainly focusing on the clinical translation from microbiome research to an accurate diagnosis, subtype classification and precision medicine.